Pengembangan Media Monopoly Smart Games Asean Dalam Meningkatkan Wawasan Global Siswa Kelas VI di Sekolah Dasar - Firmansyah A. Ishak; Haris Mahmud; Muhammad Sarlin (JAMBURA Elementary Education Journal, 2023)
Learning media in grade VI at SDN 4 Batudaa, Gorontalo Regency, is still lacking in the learning process. This fact is from the beginning of the social science learning process and the 2013 curiculum supporting books in grade VI. This causes the learning not to run properly due to the lack of learning media in the learning process. Th research is aims to develop ASEAN Smart Games Monopoly Media to increase the Global Insights of student in grade VI of SDN 4 Batudaa, Gorontalo Regency. This study is a research an development (R&D) that uses the thiagarajan procedure. There are assessments of media expert, language experts, material experts, student, and classroom teacher. This data collection techniques include questionnaires, interviews, document studies, and documentation. Based on the result, it obtains a product with a media expert assessment of 86,5 %; linguist by 89%; material experts by 98,6% with the “ very feasible”criteria. Then the product is tested. The student product trial gained 76,83% and the teacher’s response 96,5%. Based on the result, it can be concluded that the ASEAN smart games monopoly media is very feasible to be used in learning at SDN 4 Batudaa, Gorontalo Regency.